A CFD model for the coupling of multiphase, multicomponent and mass transfer physics for micro-scale simulations. (October 2017) - Soh, Gim Yau; Yeoh, Guan Heng; Timchenko, Victoria
Highlights: CFD model that couples multiphase, multicomponent and mass transfer physics developed. Volume-of-fluid (VOF) used to capture multiphase physics. Multicomponent species tracked within the correct phase. Smoothing operations used to alleviate spurious velocities enable model's use in micro-scale simulations. Test cases conducted and establishes accuracy and reliability of model. Abstract: This paper presents a CFD model that couples the physics of multiphase and multicomponent flow involving mass transfer for micro-scale simulations. The volume-of-fluid (VOF) model is utilised to capture the multiphase physics, and smoothing operations are applied in the surface tension force calculation to minimise spurious velocities. For multicomponent tracking of the species transport, the α-factor and expulsion operation methods are implemented to ensure that the species are tracked within the correct phase. Three different mass transfer models were adopted with modifications to the original models. The developed coupled multiphase-multicomponent model was assessed via a series of validation cases: a simple one-dimensional (1D) diffusion problem, horizontal vapour flow over a smooth stationary liquid where Sherwood number was used to measure mass transfer performance, and the dissolution of a two-dimensional (2D) droplet. In all the test cases, the model was able to yield reasonably close results with the analytical solution or empirical correlations used in the validation, thus establishing its accuracy and reliability of the developed model. Simulations using the coupled multiphase-multicomponent model represent a cost-effective approach to obtaining insights into the flow physics for a variety of applications: dissolution of droplets in microchannels, transport of drugs in blood vessels that entails mass transfer and simulations of carbon dioxide enhanced oil recovery at the pore-scale.